Superior cooling performance of a single channel hybrid magnetofluidic cooling device. (1st November 2020) - Varma, V.B.; Pattanaik, M.S.; Cheekati, S.K.; Ramanujan, R.V.
Graphical abstract: Highlights: Hybrid materials based superior magnetofluidic cooling device. Energy-efficient passive cooling of a heat load by simulation-driven system design. Detailed experimental, simulation, and analytical investigations. Abstract: Efficient transfer of heat is a major challenge in a plethora of industrial systems and devices. Lower device temperatures can improve energy efficiency and reduce premature device failure. We report the development of a single channel magnetofluidic cooling (MFC) device with high passive cooling performance. MFC is based on thermo-magnetofluidic (TMF) convection, i.e., spontaneous ferrofluid motion due to the gradients of external magnetic field and temperature. Our novel Cu-silicone hybrid design exhibited the highest heat load temperature drop of 183 °C, which is 3 times higher cooling than previous reports in the literature. Experimental studies of TMF flow are challenging due to the opaque nature of the ferrofluid. Hence we developed a novel TMF setup and quantified the temperature and velocity profiles. We also developed a simulation model to describe the MFC process; the results are in good agreement with our experimental findings. The high cooling performance of our device was found to be due to high vorticity and mixing. Our MFC device is useful for transferring waste heat load from a variety of systems. It is a passive, green, self-regulating, noise, and vibration-free cooling technology.